Systematics of Guntheria Womersley, 1939 and related genera of chigger mites (Acariformes: Trombiculidae) - Alexandr A Stekolnikov (Persian Journal of Acarology)
Chigger mites of the tribe Schoengastiini Vercammen-Grandjean, 1960 having five non-specialized setae on the palpal tarsus and some other genera related to Guntheria Womersley, 1939 were reviewed based on literature. Original descriptions and re-descriptions of 283 species were examined. A new classification of Guntheria was proposed, with the re-definition of the subgenera G. (Domrowana) Vercammen-Grandjean & Langston, 1971 and G. (Domrowella) Vercammen-Grandjean, 1960, and the related genus Derrickiella Audy & Domrow, 1957. The subgenus G. (Phyllacarus) Vercammen-Grandjean, 1967 was re-defined and raised to the genus level. One new subgenus was described — Phyllacarus (Platypacarus) subgen. nov. One previously monotypic genus Argentinacarus Goff & Gettinger, 1995 was expanded and included in Derrickiella as a subgenus. The genus Proschoengastia Vercammen-Grandjean, 1967 previously synonymized with Herpetacarus (Abonnencia) Vercammen-Grandjean, 1960 was restored. Two new synonyms were established: Pseudoschoengastia (Walchioides) Vercammen-Grandjean 1960 [= Guntherana (Pseudosusa) Vercammen-Grandjean, 1960, syn. nov.] and Euryphylla Vercammen-Grandjean, 1967 stat. nov. [= Eusaperium Brennan, 1970, syn. nov.]. Sixty-six new combinations were proposed in the genera Guntheria (3), Derrickiella (22), Susa Audy & Nadchatram, 1960 (1), Schoutedenichia Jadin & Vercammen-Grandjean, 1954 (2), Phyllacarus (26), Pseudoschoengastia Lipovsky, 1951 (1), Vanidicus Brennan & Jones, 1961 (1), Ornithogastia Vercammen-Grandjean, 1960 (1), Perissopalla Brennan & White, 1960 (1), Euryphylla (7), and Proschoengastia (1). A key to the genera and subgenera of Schoengastiini with five setae on palpal tarsus was compiled.